2010
DOI: 10.1007/s11250-010-9641-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and non-genetic factors affecting semen production traits in Karan Fries crossbred bulls

Abstract: The objective of the study was to evaluate the effects of genetic and non-genetic factors on production of breeding bulls and semen quality parameters in Karan Fries crossbred male by fitting least squares analysis. Genetically, the animals were divided into three subclasses. The non-genetic factors were season of birth, period of birth, and age group with three subclasses each for season of birth and period of birth. Age group was classified into four subclasses. The traits generated in the study were number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 9 publications
(7 reference statements)
2
18
0
Order By: Relevance
“…4). One of the most important reasons for poor semen quality in crossbred bulls (Khate 2005;Chauhan 2007) may be low testosterone production in these animals as observed in the present study in crossbred males.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…4). One of the most important reasons for poor semen quality in crossbred bulls (Khate 2005;Chauhan 2007) may be low testosterone production in these animals as observed in the present study in crossbred males.…”
Section: Discussionmentioning
confidence: 49%
“…However, the male crossbred offsprings are often inferior to purebreds in semen production. The proportion of males reserved for breeding and reaching successful freezing stage was lowest (29%) in Karan Fries (cross between Sahiwal or Tharparkar with Holstein Freisian cattle) and highest (45%) in Sahiwal cattle and poor semen quality was an important reason of disposal in Karan Fries bulls (Khate 2005;Chauhan 2007). Poor semen quality was found to be the main reason of disposal in adult breeding Karan Fries bulls above 3 years of age (Chauhan 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Disposal due to surplus was observed in these age groups which might be due to more number of bulls available than the requirement of the farm. At NDRI herd Chauhan (2007) conducted a study on Karan Fries males and found that important cause of disposal for male calves below 1.5 years of age was mortality and in case of above 1.5 years of age group, culling due to poor growth and poor semen quality were the main reasons. Based on 15 yrs data Mukhopadhyay et al (2010) reported that subfertility problem is one of the major causes of disposal of breeding bulls which was almost one-third to half of the reserved stock disposed due to sub-optimal reproduction efficiency and poor libido was one of the important cause of subfertility among the Murrah buffalo males.…”
Section: Resultsmentioning
confidence: 99%
“…Lal (1991) reported that morphology of calves and its dam's performance were considered as selection criteria in young bulls but later on when the animal matures, its semen characteristics like volume, colour, concentration, motility, live/death count and semen freezability were considered. Although a large number of male animals are reserved and raised for semen donation, more than half of those animals are disposed or rejected before reaching frozen semen production stage due to various reasons like offbred, disease, poor growth and health, death, abscess, wound and defective legs (Khate 2005;Chauhan 2007). Young breeding bulls are also culled on the basis of poor libido, poor semen quality and freezability (Chenoweth et al, 2003).…”
Section: Introductionmentioning
confidence: 99%